Program Konseling Keluarga Bagi Orang Tua Yang Memiliki Anak Autis - Nurhastuti Nurhastuti (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2016)
Unpreparedness of parents in taking care of the interests of children with autism will make children continue backward and not ready for the future. In such conditions it is necessary support for parents in caring for children with autism. This study was conducted aiming to provide support to parents of children with autism so that the problems arising from the existence of an autistic child can be minimized or even eliminated altogether. In addition, this research can also be used as a reference for parents who have children with autism in an effort to maintenance and cure children with autism. Qualitative research is considered more appropriate to determine the family counseling program for parents who have children with autism in the Autism Institute YPPA Padang. The approach used in this study is deemed appropriate in understanding and motivating parents of children with autism with all complexity as subjective beings.